Effect of plant density and fertility levels on growth and yield of pearl millet (Pennisetum glaucum) hybrids under limited irrigation conditions in semi-arid enviroment - Rathore, B S; Rana, V S; Nanwal, R K (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted during rainy (kharif) season of 2004 and 2005 at crop research farm of the University, Hisar, to find out suitable spacing for pearl millet (Pennisetum glaucum L.) hybrids along with N and P levels so as to increase the productivity of pearl millet. The experiment was laid out in split-plot design allocating 2 hybrids and 3 plant densities in main plots and 4 fertility levels in sub-plots replicated thrice. Highest grain yield (3.53 tonnes/ha) was recorded when the crop was sown at plant density of 45 cm x 12 cm and fertilized with 90 kg N + 45 kg P2O5/ha but was at par with 60 kg N + 30 kg P2O5ha. ’HHB 67-2’ pearlmillet hybrid recorded relatively higher value for consumptive use of water, water-use efficiency and grain yield.